Magma Signatures in the Terceira Rift Azores: a melt inclusion study - Marques, Ana Filipa (2014)
The Terceira Rift (TR) is a 550km long ESE trending line of volcanic reliefs (Graciosa Island, Terceira Island, D. João de Castro Bank, S. Miguel Island) alternating with deep basins (e.g. E of Terceira, Hirondelle) that define the plate boundary between the European and African plates on the Azores plateau [1]. Seismic tomography suggests that the Azores plume is centered NE of Terceira supplying upwelling plume material SW of Terceira (e. g. Faial) [2]. Melt inclusions (MI) are small portions of melt trapped during crystal growth. Their study allows the characterization of the composition of primary melts, mantle heterogeneity, magma sources and timescales. This study presents the first ge ochemical dataset of olivine - hosted unexposed MI sampled from submarine and subaereal lavas along the TR. Plots of incompatible trace element ratios (Fig.1) confirm the presence of distinct mantle signatures showing a mixing trend between two end-members that represent extreme topographic domains: Terceira and Hirondelle Basin. These findings will be discussed considering recent geophysical and geochemical data obtained in the area.